Penanganan resesi gingiva Miller klas I-II menggunakan platelet-rich fibrin dan subepithelial connective tissue graft Treatinggingival recessionMiller’s class I-II usingplatelet-richfibrinandsubepithelial connective tissue graft - Mientje Tengkawan; Sri Oktawati; Arni Irawaty Djais; Burhanuddin DP (Journal of Dentomaxillofacial Science, 2013)
Platelet-rich fibrin (PRF) is the generation of platelet concentrates containing growth factors, which play a role in theprocess of healing and tissue regeneration. This study aimed to compare the effects of using of PRF with subepithelialconnective tissue graft (SCTG)as a treatment to gingival recession Miller Class I-II. Nine patients with bilateralgingival recession, as the subjects have two recessions. One side was treated with coronally advanced flap(CAF)+SCTG, while the other side was treated with CAF+PRF. The length of the recession is measured andcalculated as the percentage of root closure before and after surgery (10 and 30 days). The results showed that therewere significant differences in the average length of recessions between PRF and SCTG before and after the action onday 10 and day 30 (p<0.05). Closing percentage of gingival recession 10 days after SCTG treatment was 7 (77.8%)had experienced completely closing; while the PRF, only 6 (66.7%); p>0.05. Whereas on day 30, after SCTGtreatment, all subjects had undergone a recession closing perfectly, while the PRF group only 66,7% recession thathave closing completely (p=0.05). It was concluded that the CAF+SCTG provide maximum results compared withCAF+PRF in treating gingival recession Miller Class I–II.